Enhancing SME Performance through Digital Finance: Do Digital Finance Accessibility and Digital Financial Literacy Matter? - Santoso, Eko Esti; Normawati, Rani Arifah; Latifah , Nunuk (Economics, Business, Accounting & Society Review, 2025)
Small and Medium Enterprises (SMEs) are a vital driver of economic growth in developing countries, yet they remain highly vulnerable to market disruptions and external shocks. The rapid expansion of digital finance has created both opportunities and challenges, underscoring the importance of digital financial literacy and accessibility in sustaining SME performance. Despite increasing attention to inclusive finance, empirical evidence directly linking digital financial literacy, digital finance accessibility, and SME performance remains limited, particularly within developing economy contexts such as Indonesia. This study aims to investigate the effects of digital financial literacy and digital finance accessibility on SME performance, with digital finance adoption examined as a mediating variable. Employing a quantitative research design, data were collected through surveys of 430 SMEs across two provinces in Indonesia and analyzed using SEM-PLS. The results reveal that both digital financial literacy and digital finance accessibility significantly and positively influence digital finance adoption and SME performance. Moreover, digital finance adoption partially mediates the relationship between digital financial literacy and performance, while no mediation effect is observed for digital finance accessibility. The findings highlight the need to strengthen SMEs’ digital financial literacy as a strategic resource and to improve access to digital financial infrastructure. For policymakers and practitioners, these results emphasize the importance of capacity-building and inclusive digital ecosystems to enhance resilience and competitiveness among SMEs.